2002
DOI: 10.1037/0022-0167.49.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Association between childhood physical and emotional abuse and disordered eating behaviors in female undergraduates: An investigation of the mediating role of alexithymia and depression.

Abstract: Although disordered eating behaviors are relatively common among college women, many questions about their etiology remain. In the present study, structural equation modeling was used to investigate potential mediating associations among variables previously found to be associated with the continuum of disordered eating behaviors in a large sample of college women. Results indicated that family conflict, family cohesion, and childhood physical and emotional abuse and neglect were not directly associated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
125
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 118 publications
12
125
0
2
Order By: Relevance
“…This can be interpreted to mean that particularly in bulimic subjects with a high degree of psychiatric comorbidity, a traumatic history is probable (Brewerton, 2004;Thompson & Wonderlich, 2004). Other traumata found in samples of ED patients were physical (Rorty, Yager, & Rossotto, 1994) and emotional abuse (Kent, Waller, & Dagnan, 1999), teasing and bullying (Mazzeo & Espelage, 2002), parental break-up and loss of a family member (Dalle et al, 1996;Mahon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This can be interpreted to mean that particularly in bulimic subjects with a high degree of psychiatric comorbidity, a traumatic history is probable (Brewerton, 2004;Thompson & Wonderlich, 2004). Other traumata found in samples of ED patients were physical (Rorty, Yager, & Rossotto, 1994) and emotional abuse (Kent, Waller, & Dagnan, 1999), teasing and bullying (Mazzeo & Espelage, 2002), parental break-up and loss of a family member (Dalle et al, 1996;Mahon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…30 Researchers have searched for factors that mediate the relationship of a history of childhood abuse and eating disorders in various populations, although not in gay and bisexual men. Among the factors that have been suggested are psychological factors, such as dissociation, 31 general distress, 30,32 anxiety, 31 depression, 33 substance abuse, 22 and alexithymia (an unawareness or inability to talk about feelings or emotions 30,32,33 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is consistent evidence that alexithymia is elevated in people with eating disorders (Beales & Dolton, 2000;Carano et al, 2006;Cochrane, Brewerton, Wilson, & Hodges, 1993;De Panfilis, Salvatore, Avanzini, Gariboldi, & Maggini, 2001;Kessler, Schwarze, Filipic, Traue, & von Wietersheim, 2006;Mazzeo & Espelage, 2002;Pinaquy, Chabrol, Simon, Louvet, & Barbe, 2003;ZonneyvilleBender, van Goozen, Cohen-Kettenis, van Elburg, & van Engeland, 2002;Zonnevylle-Bender et al, 2004), problematic gambling (Lumley & Roby, 1995;Parker, Wood, Bond, & Shaughnessy, 2005), and alcohol and drug abuse or dependence (El Rasheed, 2001;Haviland, Hendryx, Shaw, & Henry, 1994;Kauhanen, Julkunen, & Salonen, 1992), although perhaps not cigarette smoking and nicotine dependence (Lumley, Downey, Stettner, Wehmer, & Pomerleau, 1994). One comprehensive study found that compared with controls, patients with eating disorders or alcohol-or drugrelated disorders had similar, high levels of alexithymia, and a path analysis suggested that alexithymia predicted depression that predicted the addictive behavior in these disorders (Speranza et al, 2004).…”
Section: Does Alexithymia Contribute To Unhealthy Behavior?mentioning
confidence: 99%